2015
DOI: 10.1002/ijc.29601
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs and the risk of head and neck cancer: A case‐control analysis

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) and acetylsalicylic acid (aspirin) have been associated with a reduced risk for certain cancers. We explored the association between use of NSAIDs and the risk of head and neck cancer (HNC). We conducted a case-control analysis in the UK-based Clinical Practice Research Datalink (CPRD) among people below the age of 90 years with incident HNC between 1995 and 2013. Six controls per case were matched on age, sex, calendar time, general practice, and number of years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…NSAID is a group of drugs commonly prescribed during the treatment of periodontal disease. Though the results are not consistent, the potential chemo-preventive effect of NSAIDs for oral and pharyngeal cancer had been studied and suggested recently [36][37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…NSAID is a group of drugs commonly prescribed during the treatment of periodontal disease. Though the results are not consistent, the potential chemo-preventive effect of NSAIDs for oral and pharyngeal cancer had been studied and suggested recently [36][37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…Our finding of decreased risk estimates among long‐term consistent nonaspirin NSAID users supports previous studies reporting reduced HNC risk in ibuprofen users, who take the medication daily or had ≥6 prescriptions issued . Similar to our results, these studies found no association between HNC risk and ever‐use of nonaspirin NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The literature assessing risk of HNC in relation to use of NSAIDs has primarily focused on aspirin use and reported equivocal results. Only few observational studies have examined the association between nonaspirin NSAID use and risk of HNC and the results are inconsistent . Limitations of these studies include small sample sizes, self‐reported exposure information and lack of both information on potential confounders as well as thorough assessments of patterns of use (dose–response relationships).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many chemical or natural inhibitors of the PLA 2 pathway show antitumor effects and may be potential anti-cancer drugs 19 24 . Some non-steroidal anti-inflammatory drugs that inhibit the prostaglandin pathway (COX-2), such as Ibuprofen, have been described as potentially reducing the risk of cancer 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%